PENGARUH SHARIA COMPLIANCE TERHADAP KINERJA KEUANGAN DENGAN MEDIASI KINERJA MAQASHID SYARIAH PADA PERBANKAN SYARIAH - Desta, Sri Yulfa; Subagiyo, Rokhmat; Usdeldi, Usdeldi (IAIN Tulungagung, 2022)
This study aimed to prove that the mediation of the performance of sharia maqashid affects sharia compliance with financial performance. The method used was a regression analysis based on Structural Equation Modeling with panel data available in the annual reports published by Islamic commercial banks in Indonesia for the period 2014-2019. The results of the study proved that sharia compliance has a direct and significant negative influence on financial performance. However, sharia compliance does not have a significant effect on maqashid sharia performance. Furthermore, maqashid sharia performance has a negative and significant effect on financial performance, but does not mediate the influence of sharia compliance on financial performance at Islamic commercial banks in Indonesia. This research recommends that policymakers confirm regulations regarding the implementation and disclosure of sharia compliance and maqashid sharia performance indicators in the annual reports of Islamic Conventional Banks (ICBs). In addition, it is necessary to design an integrated Islamic banking performance measurement model that includes conventional financial performance indicators with maqashid sharia performance indicators. In practical implementation, ICBs should increase the implementation of sharia compliance and maqashid sharia performance indicators.